AL WAZHIFAH AL ‘ĀMMAH (PELAYANAN PUBLIK DALAM LEMBAGA KEUANGAN SYARIAH) - Maulidhany, Dicky (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2020)
This paper discusses the quality of public services from Islamic banking. Quality of service is one of the important things for customers or customers compared to companies engaged in the company. Quality of service can be realized through its employees, among others: honest, humble service and services in accordance with Islam. Some aspects of the quality of this compilation are applied together to build a very good and satisfying quality service, so as to ensure a sizable quality of service in choosing priorities to use services which in this case is to save Islamic financial institutions. Keywords: Quality, paradigm, public service